Money in the Bank--Lessons Learned from Past Counterinsurgency (COIN) Operations - Rabasa, Angel; Chalk, Peter; Khilko, Ivan; Shukla, Paraag; Warner, Lesley Anne (RAND Corporation, 2023)
Six historic counterinsurgency (COIN) operations are examined to determine which tactics, techniques, and procedures led to success and which to failure. The Philippines, Algeria, Vietnam, El Salvador, Jammu and Kashmir, and Colombia were chosen for their varied characteristics relating to geography, historical era, outcome, type of insurgency faced, and level of U.S. involvement. Future U.S. COIN operations can learn from these past lessons.